(untitled) (Research, Society and Development, 2023)
The choice of learning activities has an impact on language learning. However, teachers do not always consider a learning outcome for each activity. Therefore, this research set out to identify if teachers consider learning outcomes in their planning, additionally, to identify the most common learning outcomes in the activities they choose for the classroom. This qualitative descriptive research methodology collected data through semi-structured interviews. Ten in-service teachers and ten student-teachers participated in the study. Data was analyzed using iterative content analysis. Results showed that teachers do not reflect learning outcomes for activities in their planning, but they do consider learning outcomes for their whole lessons. Analysis showed that outcomes mostly fall in the application and comprehension domains. It was concluded that teachers probably implement activities that go from controlled practice to production following the PPP approach. Results can be explained by the importance that teachers and institutions give to the practice and production of the language.